Utilizing the Cholecystagogue, Ensure Plus, Results in Similar Hepatobiliary Scintigraphy Study Results and Patient Outcomes Status Post Cholecystectomy, in Comparison With Sincalide. (January 2020) - Peacock, Justin G.; Katchen, Jared M.; Christensen, Chad T.; Banks, Kevin P.
Abstract : Objective: To determine if use of the oral cholecystagogue, Ensure Plus (EP), in hepatobiliary scintigraphy (HBS) leads to a similar distribution of normal and abnormal gallbladder ejection fractions (GBEFs) versus other historical secondary findings of chronic biliary disease in a similar patient population compared with the conventional cholecystokinin analog, sincalide. The HBS findings analyzed included the GBEF, small bowel transit time, gallbladder fill time, and reversal of the normal gallbladder versus small bowel transit. The secondary objectives were to determine whether patient outcomes were significantly different for EP and sincalide HBS study patients following cholecystectomy, namely, the surgical pathology and patient-reported biliary-type pain. Methods: We reviewed all HBS examinations over a retrospective 34-month period. Data from 446 patients who underwent sincalide or EP HBS with GBEF determination for evaluation of chronic symptoms concerning for biliary etiology met the inclusion criteria. The aforementioned HBS findings and postsurgical patient outcomes were obtained for each patient group. Results: Comparing HBS examinations performed with sincalide or EP, no significant differences were noted in the major HBS findings of similar patient populations. Outcomes for the sincalide and EP groups status post cholecystectomy were assessed to determine their sensitivity, specificity, positive predictive value, and negative predictive value. The outcomes assessed were the histopathology and patient-reported amelioration of biliary-type pain. No significant differences were noted. Conclusions: The sincalide and EP cholecystagogues did not lead to significantly different HBS findings for similar patient populations or postcholecystectomy outcomes.